Avaliação temporal de atributos físicos de um solo construído em área de mineração de carvão recuperado com gramíneas perenes. - Castro, Rafaela Costa de (2012)
The Candiota region has the largest coal reserve in Brazil, known as the Big Candiota deposit. In this locality the coal lies near the surface, being open-pit mining. This method of extraction involves removing the horizons A and / or B of the original soil, followed by removal of rocks with subsequent replacement of sterile armholes open. The sterile are leveled by bulldozer and is the replacement of topsoil original, finalizing the construction process from the ground. This process entails a large compression generated by intense and repeated traffic of heavy equipment over the area, restricting the establishment of vegetation for long periods. The impacts caused by the topographic reconstruction of the area are reflected in soil physical built, being directly related to the structure, being the density values and high disproportionality between micro and macropores the first negative effects to be observed. The use of plants that act as soil decompressor is an important strategy in recovering the structural quality of soil. The aim of the study was to analyze the potential of differentcover crops on reclamation by coal mining, through the determination of physical parameters of soil built over time. Treatments were analyzed with perennial grasses of summer, implanted in November / December 2003: T1 - Hemártria (Hemarthria altíssima), T4 - Pensacola (Paspalum notatum), T5 - Grama Tifton (Cynodon dactilon), T7- Braquiária brizanta (Brachiaria brizantha). As a control the ground built without cover crops was used SCSP, in order to observe the action of the plants in the recovery of built soil attributes. As general conclusions, after six years of experiment, the initial recovery of physical indicators of built soil was observed, proving the efficiency of perennial grasses to rehabilitate structure of soil built along the time.